KARAKTERISTIK BRIKET ARANG SEKAM PADI DENGAN VARIASI KONSENTRASI PEREKAT TAPIOKA DAN SAGU - Rohmat Musafah; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to obtain the best concentration of tapioca and sago adhesive on briquettes from rice husk. This research was conducted experimentally using Completely Randomized Design (CRD) with six treatments and three replications and continued with Duncan's New Multiple Range Test (DNMRT) at level of 5%. The treatments were BTS1 (Tapioca adhesives 0%: Sago adhesives 5% from total ingredients), BTS2 (Tapioca adhesives 4%: Sagoadhesives 1% from total ingredients), BTS3 (Tapioca adhesives 2%: Sago adhesives 3% from total ingredients), BTS4 (Tapioca adhesives 3%: Sago adhesives 2% from  total ingredients), BTS5 (Tapioca adhesive 4%: Sago adhesives 1% from  total ingredients), and BTS6 (Tapioca adhesive 5%: Sago sadhesives 0% from  total ingredients). The results of analysis of variance showed that the variation of tapiocaand sago adhesive concentration had significantly effect on water content, volatile content, calorific value and carbon boundedcontentbut gave no significantly effect to ash content. The best quality of briquette was BTS6(Tapioca adhesive 5%: Sago adhesives 0% from total ingredients) produced water content 4.14%, ash content 5.98%, calorificvalue 3155.87 K /g, evaporate 38.95%, and carbon bounded content 50.93%. Keywords:Briquettes, rice husk, adhesive, tapioca, sago.